Acceptability and User Satisfaction of a Smartphone-Based, Interactive Blood Glucose Management System in Women With Gestational Diabetes Mellitus - Hirst, Jane E.; Mackillop, Lucy; Loerup, Lise; Kevat, Dev A.; Bartlett, Katy; Gibson, Oliver; Kenworthy, Yvonne; Levy, Jonathan C.; Tarassenko, Lionel; Farmer, Andrew (Journal of diabetes science and technology, 2015)
Background: The increase in gestational diabetes mellitus (GDM) is challenging maternity services. We have developed an interactive, smartphone-based, remote blood glucose (BG) monitoring system, GDm-health. Aims: The objective was to determine women’s satisfaction with using the GDm-health system and their attitudes toward their diabetes care. Methods: In a service development program involving 52 pregnant women (September 2012 to June 2013), BG was monitored using GDm-health from diagnosis until delivery. Following birth, women completed a structured questionnaire assessing (1) general satisfaction, (2) equipment issues, and (3) relationship with the diabetes care team. Responses were scored on a 7-point Likert-type scale. Reliability and validity of the questionnaire were assessed using statistical methods. Results: Of 52 women, 49 completed the questionnaire; 32 had glucose tolerance test confirmed GDM (gestation at recruitment 29 ± 4 weeks (mean ± SD), and 17 women previous GDM recommended for BG monitoring (18 ± 6 weeks). In all, 45 of 49 women agreed their care was satisfactory and the best for them, 47 of 49 and 43 of 49 agreed the equipment was convenient and reliable respectively, 42 of 49 agreed GDm-health fitted into their lifestyle, and 46 of 49 agreed they had a good relationship with their care team. Written comments supported these findings, with very positive reactions from the majority of women. Cronbach’s alpha was .89 with factor analysis corresponding with question thematic trends. Conclusions: This pilot demonstrates that GDm-health is acceptable and convenient for a large proportion of women. Effects on clinical and economic outcomes are currently under investigation in a randomized trial (clinicaltrials.gov NCT01916694).